Dampak Negatif Pernikahan Dini Pada Kehidupan Anak dalam Karya Seni Lukis Surealis - Wella Monica Ardilla; Nessya Fitryona; Ferdian Ondira Asa (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This final work aims to visualize the various negative impacts caused by early marriage on the lives of children resulting from the marriage in a surrealist painting. The hope of this work is to increase public knowledge and awareness and enrich ideas in realizing surrealist painting. The method used by the author is the art concertium method which consists of: (1) Preparation, in the form of observation, collection of information and ideas. (2) Elaboration, to determine the main idea through analysis, abstraction, generalization, and transmutation. (3) Synthesis, to realize the concept of the artwork. (4) Realization of the concept into various art media. (5) Completing it into the final form of the artwork. These stages are a reference for the author in working on the painting. Based on the understanding and determination of the idea, the author can visualize 10 works with the titles: first "Cage", second "Control", third "Silent", fourth "Gloomy", fifth "Free", sixth "Grow", seventh "Towards Light", eighth "Tertindih", ninth "Melebur", tenth "Anger".